The Existency of English Vocabulary Learning Strategies Through Online Learning - Amaliyah, Suci; Sufyan, Agus (Tarling : Journal of Language Education, 2023)
The lack of students’ awareness of comprehensively learning English became the significant issue. The initiation to discover a suitable strategy to adopt is needed. The methodology used was mixed-method (quantitative and qualitative). Two instruments used were a questionnaire and open-ended interview questions. The data analysis was SPSS and descriptive qualitative. The research involved three senior high school classes voluntarily participated students. Based on six strategies, respondents’ answers are coded by R (Repeating vocabulary), RM (Repeating in mentioning vocabulary like a native), and RP (Repeating vocabulary in physical actions), WN (Writing Vocabulary Note), WD (Writing Diary), and WS (Writing Summary), RN (Reading English Novel), RS (Reading Strategy), and RL (Reading Light Books), LD (Look up in the dictionary) and LED (Look Up in Electronic Dictionary), GE (Guessing with Gesture), and GN (Guessing the next word). The repeating strategy became the students’ most preferred strategy (M=3.52), while guessing (M=2,99) became the most unpreferred strategy. Therefore, the researcher attempts to conduct this research to investigate students’ preference strategy and discover the urgency.